The Impact of Transformation of Farmers’ Livelihood on the Increasing Labor Costs of Grain Plantation in China - Xilong Jiang (MDPI AG, 2021)
Analyzing the recessive impacts of farmers’ livelihood transformation on the surging labor cost in grain production is conducive to finding optimization paths for grain production. This study developed the Residual Livelihood Ratio (RLR) and the Livelihood Simpson Index (LSI) to measure the transformation of farmers’ livelihood in China, and applied the multiple regression model to explore the influence of the transformation of farmers’ livelihood on the labor cost of grain production. The results show that because of the soaring increment in labor cost, the net profit of rice, wheat, and maize production decreased largely in China. The LSI increased, while the RLR decreased, which indicated that farmers’ livelihoods transitioned towards a more unbalanced income–expenditure but more flexible employment. The Residual Livelihood Ratio; the mechanization input; the grain yield per unit area; the non-grain plantation degree; and the non-agricultural land use degree showed negative impacts on labor cost in grain production, whereas the Livelihood Simpson Index and Engel’s coefficient of farmers showed positive impacts on the labor cost. This paper proposes targeted policy implications for labor cost control of the grain production in China.